Dermatological manifestations during COVID‐19 and histological picture: Description of two clinical cases. Issue 5 (23rd February 2021) - Mencarini, Paola; Scarabello, Alessandra; Del Nonno, Franca; Lalle, Eleonora; Falasca, Laura; Gualano, Gina; Nardacci, Roberta; Mosti, Silvia; Musso, Maria; Libertone, Raffaella; Di Bari, Virginia; Rosati, Silvia; et al.
Abstract: It is not yet entirely clear what is the relevance of skin symptoms and what clinical implications are related to their appearance in COVID‐19 patients. We describe two cases of COVID‐19‐associated pneumonia, which presented skin manifestations in advanced stage of illness, when nasopharyngeal swabs became negative for SARS‐CoV‐2. The first case presented erythematous, maculopapular lesions; the second developed petechial, vesicular and blood‐encrusted lesions on the limbs. Histopathology documented perivascular lymphocytic infiltrates, with prevalent CD4+ T‐cells in both patients. The research of SARS‐CoV‐2 in tissues with real time RT‐PCR was negative. Basal keratinocytes displayed C4d deposits in one case, who developed laboratory signs indicative of a procoagulative condition at the same time as the skin rash. Skin manifestations during SARS‐CoV‐2 infection seem to be clinically relevant and further studies are necessary to assess if they are linked to systemic complications, lack of viral clearance or cascades of immune responses induced by the virus, even in patients affected by mild pneumonia.